Chinese students' perceptions of teacher–student interpersonal behavior and implications. (December 2015) - Wei, Michael; Zhou, Yalun; Barber, Carolyn; den Brok, Perry
Abstract: Students' perceptions are one of the most important elements in evaluating the learning environment. Although the literature is replete with studies investigating teacher-student interpersonal behavior in science classrooms, relatively few studies have been conducted in foreign language classrooms, and in countries like China. The researchers in this study investigated the perceptions of teacher–student interpersonal behavior in English as a Foreign Language (EFL) classrooms in China. A total of 823 students from 19 classes taught by 9 teachers were asked to assess their teachers' actual and ideal interpersonal behavior using the Questionnaire on Teacher Interaction (QTI). Results showed that, on actual interpersonal teacher's behaviors, Chinese students reported higher scores for Leadership, Helpful/Friendly, Understanding, Student Freedom and Strict; and lower scores for Uncertain, Dissatisfied, and Admonishing. On ideal interpersonal teacher's behaviors, Chinese students indicated even higher scores for Leadership, Helpful/Friendly, Understanding, Student Freedom, but lower scores for Dissatisfied, Admonishing, and Strict. Implications will be discussed.